2019
DOI: 10.1038/s41467-019-12023-w
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in patterns of germline mutation between mice and humans

Abstract: Whole genome sequencing (WGS) studies have estimated the human germline mutation rate per basepair per generation (~1.2 × 10 −8 ) to be higher than in mice (3.5–5.4 × 10 −9 ). In humans, most germline mutations are paternal in origin and numbers of mutations per offspring increase with paternal and maternal age. Here we estimate germline mutation rates and spectra in six multi-sibling mouse pedigrees and compare to three multi-sibling human pedigrees. In both speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
93
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 36 publications
20
93
2
Order By: Relevance
“…This result differs from humans, where the male bias seems constant over time (Gao et al 2019), but more time points in macaque would be needed to interpret the contribution over time. In rhesus macaques, the ratio of paternal to maternal contribution to the shared mutations between related individuals is 1:1, similarly to what has been shown in mice (Lindsay et al 2019), highlighting that those mutations probably occur during primordial germ cell divisions in postzygotic stages. Our study shows many shared patterns in the de novo mutations among non-Hominid primates.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This result differs from humans, where the male bias seems constant over time (Gao et al 2019), but more time points in macaque would be needed to interpret the contribution over time. In rhesus macaques, the ratio of paternal to maternal contribution to the shared mutations between related individuals is 1:1, similarly to what has been shown in mice (Lindsay et al 2019), highlighting that those mutations probably occur during primordial germ cell divisions in postzygotic stages. Our study shows many shared patterns in the de novo mutations among non-Hominid primates.…”
Section: Discussionsupporting
confidence: 75%
“…Due to higher sperm competition in rhesus macaque, the replication might be under selective pressure for fast production at the expense of replication fidelity, leading to less DNA repair mechanisms. As in other primates, we found a male bias in the contribution of de novo mutations, as the paternal to maternal ratio is 4.2:1.This ratio is higher than the 2.7:1 ratio observed in mice (Lindsay et al 2019) and slightly higher than the 4:1 ratio observed in humans (Goldmann et al 2016;Jónsson et al 2018;Lindsay et al 2019). Similarly to the wild, the males of our dataset reproduced from 10 years old, which did not allow us to examine if the contribution bias was also present just after maturation.…”
Section: Discussionsupporting
confidence: 61%
“…For comparison, there are only a few other studies that have leveraged whole-genome sequencing to measure mutation rates in inbred strains of mice (Table 2). Lindsay et al (2019) and Adewoye et al (2015) sequenced several groups of inbred strain parents and their offspring and estimated mutation rates of 3.9 × 10 −9 (CIs: 3.7-4.2 × 10 −9 ) and 3.8 × 10 −9 (CIs: 3.0-4.6 × 10 −9 ), respectively, and Miholland et al (2017) did a similar study with two parents and two offspring, resulting in an estimate between 6.7 and 7.0 × 10 −9 . In these three cases, per nucleotide per-generation mutation rates were calculated using the number of unique SNVs observed in the offspring and the number of nucleotides that passed filtering.…”
Section: Discussionmentioning
confidence: 99%
“…A paternal mutational bias has long been hypothesized for diploid sexually reproducing organisms based on the idea that the increased number of cell divisions in sperm versus egg should lead to higher numbers of mutations in the male germline than the female germline (Haldane, 1947;Kong et al, 2012;Lindsay et al, 2019). Indeed, a strong paternal mutation rate bias has been observed in the vast majority of pedigree-based mutation rate estimates to date (Gao et al, 2019;Lindsay et al, 2019;Rahbari et al, 2016;Thomas et al, 2018;Venn et al, 2014) and in many studies of phylogenetically-based rates (Axelsson et al, 2004;Ellegren and Fridolfsson, 1997;Goetting-Minesky and Makova, 2006;Shimmin et al, 1993;Zhang, 2004). The 1.2 ratio of paternal-to-maternal mutations in gray mouse lemur observed here is considerably lower than the range between 2.1 and 5.5 observed in other primate species (Gao et al, 2019;Lindsay et al, 2019;Rahbari et al, 2016;Thomas et al, 2018;Venn et al, 2014) and 2.7 in mouse (Lindsay et al, 2019).…”
Section: Reduced Male Mutational Biasmentioning
confidence: 99%
“…Indeed, a strong paternal mutation rate bias has been observed in the vast majority of pedigree-based mutation rate estimates to date (Gao et al, 2019;Lindsay et al, 2019;Rahbari et al, 2016;Thomas et al, 2018;Venn et al, 2014) and in many studies of phylogenetically-based rates (Axelsson et al, 2004;Ellegren and Fridolfsson, 1997;Goetting-Minesky and Makova, 2006;Shimmin et al, 1993;Zhang, 2004). The 1.2 ratio of paternal-to-maternal mutations in gray mouse lemur observed here is considerably lower than the range between 2.1 and 5.5 observed in other primate species (Gao et al, 2019;Lindsay et al, 2019;Rahbari et al, 2016;Thomas et al, 2018;Venn et al, 2014) and 2.7 in mouse (Lindsay et al, 2019). It is identical, however, to the ratio found in collared flycatchers (Smeds et al, 2016), which suggests that the low sex bias ratio observed in the gray mouse lemur is not unreasonable in the larger context of vertebrates.…”
Section: Reduced Male Mutational Biasmentioning
confidence: 99%